Sociology of ethnicity and social-change - model of rootedness and rootlessness - Abramson, Harold J. (Economic & Social Studies, 1976)
In the light of mounting interest in, and manifestations of, ethnicity in most of the world today, it becomes important to work on the broader meaning of ethnicity from the comparative, historical and theoretical perspectives. The sheer persistence and the re-emergence of ethnic identities, and the relationship of ethnic movements and developments to economic and political realities, are certainly major research issues. In this context, we might be able to learn more about ethnicity per se, if we ask questions about the alternatives and opposites to ethnicity. Just as we can better understand the social meaning of conformity by examination of the variations of deviance, so may be treated the sociology of ethnicity. Furthermore, this approach, if valid, may differentiate not only between ethnicity and its absence, but also distinguish among degrees of ethnicity as well. It is, of course, a traditional approach in sociological theory, that of deviant case analysis, or of examining one kind of phenomenon in order to undestand its mirror image or images. In this paper, then, it is proposed to define ethnicity, ethnic culture and structure; and then proceed to examine the theoretical possibilities which emerge from a proposed four-fold classification of attachments to cultural and structural entities.
Keywords: Ethnicity; Ethnic Identity